Dialoguing with teachers at school about sexuality and sexually transmitted diseases - Eveline Pinheiro Beserra; Cibele Almeida Torres; Maria Grasiela Teixeira Barroso (Rev Rene)
Our experience in school context shows us vulnerability points to which adolescents are exposed due to both the age and shortage of information about the process of becoming an adolescent. Thus, we aim to report a workshop on health education with teachers about sexuality and sexually transmitted diseases. It is an experience report, described from a workshop with twelve teachers from a public school in the state of Ceará and carried out in May, 2007. The teachers gave importance to this theme. They believe school and family form an interconnected group in youngsters’ education for a safe sexual practice. They brought forward their difficulties and recognized they are not prepared to approach this subject. Actions to permit the articulation between health and school favor means for the youngsters to accomplish better life quality through reflection about their attitudes